2021
DOI: 10.1111/maps.13700
|View full text |Cite
|
Sign up to set email alerts
|

Melt inclusions in chassignite NWA 2737: A link between processes recorded in Martian meteorites and rocks at Gale crater

Abstract: Northwest Africa (NWA) 2737, one of the only three discovered Martian chassignites, provides critical constraints on the evolution of the Martian mantle and crust. Because of chassignites' cumulative nature, they contain abundant melt inclusions (MI). MI are small droplets of melts trapped by crystals during the cooling of magma. They are critical to the study of pre-eruptive parental magma compositions, and thus, provide snapshots of the composition and evolution of Martian magmatic systems. Here, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 110 publications
(190 reference statements)
0
2
0
Order By: Relevance
“…Controversy exists regarding the proposed compositions for the chassignite parental magma, as experiments and models utilizing these compositions under various water (dry to 2 wt%) and pressure conditions (up to 15.7 kbar) have been unable to reproduce the commonly found hydrous phase, kaersutite, in NWA 2737 melt inclusions (Filiberto, 2008;Nekvasil et al, 2007). Crystallization paths compared with in situ Martian compositions also suggested that the parental liquid to chassignites could have gone through assimilation and could be more Mg-and Al-rich than previously proposed (Ostwald et al, 2022;Wu et al, 2021). These findings highlight the potential for revised compositions that can accurately reproduce the observed phases in these melt inclusions.…”
Section: Application Of Nano-xct In Estimating Bulk Composition Of Me...mentioning
confidence: 88%
See 1 more Smart Citation
“…Controversy exists regarding the proposed compositions for the chassignite parental magma, as experiments and models utilizing these compositions under various water (dry to 2 wt%) and pressure conditions (up to 15.7 kbar) have been unable to reproduce the commonly found hydrous phase, kaersutite, in NWA 2737 melt inclusions (Filiberto, 2008;Nekvasil et al, 2007). Crystallization paths compared with in situ Martian compositions also suggested that the parental liquid to chassignites could have gone through assimilation and could be more Mg-and Al-rich than previously proposed (Ostwald et al, 2022;Wu et al, 2021). These findings highlight the potential for revised compositions that can accurately reproduce the observed phases in these melt inclusions.…”
Section: Application Of Nano-xct In Estimating Bulk Composition Of Me...mentioning
confidence: 88%
“…For cumulate rocks where bulk chemistry cannot be used directly to define their magmatic source compositions, olivine‐hosted melt inclusions (droplets of magmatic liquid trapped inside growing crystals) are used to estimate the parental magma compositions. The study of melt inclusions has been extensively applied in extraterrestrial materials, as demonstrated by classic research on lunar meteorites and chondrites (Roedder, 1981; Roedder & Weiblen, 1971; Sorby, 1864) and in Martian cumulate meteorites (Filiberto, 2008, 2017; Goodrich et al., 2013; He et al., 2013; Johnson et al., 1991; Nekvasil et al., 2007; Ostwald et al., 2022; Wu et al., 2021). Both lunar and Martian meteorites contain crystallized melt inclusions within olivine, varying in size (Johnson et al., 1991; Roedder & Weiblen, 1971).…”
Section: Introductionmentioning
confidence: 99%